International Importance of Robust Breast Device Registries. Issue 2 (February 2015) - Cooter, Rodney D.; Barker, Shane; Carroll, Sean M.; Evans, Gregory R. D.; von Fritschen, Uwe; Hoflehner, Helmut; Le Louarn, Claude; Lumenta, David B.; Mathijssen, Irene M. J.; McNeil, John; Mulgrew, Stephen; Mureau, Marc A. M.; et al.
Abstract : Background: Breast implants are high-risk devices that have been at the epicenter of much debate and controversy. In light of the Poly Implant Prothèse crisis, data registries among 11 national societies around the world are cooperatively calling for the urgent need to establish robust national clinical quality registries based on international best practice within a framework of international collaboration. Methods: A survey was conducted on the historic and current status of national breast device registries. Eleven countries participated in the study, illustrating different data collection systems and registries around the world. Data collection was designed to illustrate the capabilities of current national registries, with particular focus on capture rate and outcome reporting mechanisms. Results: A study of national breast implant registries revealed that less than half of the participating countries had operational registries and that none of these had adequately high data capture to enable reliable outcome analysis. The study revealed that the two most common problems that discouraged participation are the complexity of data sets and the opt-in consent model. Conclusions: Recent implant crises have highlighted the need for robust registries. This article argues the importance of securing at least 90 percent data capture, which is achievable through the opt-out consent model. Since adopting this model, the Australian Breast Device Registry has increased data capture from 4 percent to over 97 percent. Simultaneously, it is important to foster international collaboration from the outset to avoid duplication of efforts and enable the development of effective international early warning systems.